A Highly Sensitive Perovskite/Organic Semiconductor Heterojunction Phototransistor and Its Device Optimization Utilizing the Selective Electron Trapping Effect. Issue 13 (6th May 2019) - Luo, Lin‐Bao; Wu, Guo‐An; Gao, Yang; Liang, Lin; Xie, Chao; Zhang, Zhi‐Xiang; Tong, Xiao‐Wei; Wang, Tao; Liang, Feng‐Xia
Abstract: Hybrid organic–inorganic perovskite materials have recently attracted attention due to their impressive physical properties and promising application in future optoelectronic devices and systems. In this study, a high‐performance and broadband photodetector comprising vertically stacked Cs‐doped formanidinium lead iodide (FAPbI3 ) perovskite/dinaphtho[2, 3‐ b :2′, 3′‐ f ]thieno[3, 2‐ b ]thiophene heterojunction, which shows a high responsivity of 778 A W −1 and a specific detectivity of 1.04 × 10 13 Jones, is reported. In addition, the photodetector displays excellent stability and broadband responsivity to illumination ranging from deep‐ultraviolet to near‐infrared light. It is interesting to note that doping a small amount of [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PCBM) into the perovskite film results in a substantial increase in responsivity, specific detectivity, and photoconductive gain. Specifically, the specific detectivity is as high as 7.96 × 10 13 Jones, which is much higher than that of other devices with similar geometries. The device optimization can be ascribed to an enhanced electron–hole separation ability and increase in electron accepting sites that can selectively trap electrons in the perovskite–PCBM bulk heterojunction, according to results from the experimental analyses. Abstract : In this study, a high‐performance and broadband phototransistor composed of vertically stacked Cs‐doped FAPbI3 perovskite/dinaphtho[2, 3‐b:2′, 3′‐f]thieno[3, 2‐b]thiophene (DNTT) heterojunction, with good ambient stability, is developed.